Expenditure Food and Nonfood in South Sulawesi Before and During the Covid-19 Pandemi - Aslim Husain; Drajat Martianto; Ikeu Ekayanti (Sarana Ilmu Indonesia (salnesia), 2022)
The impact of the Covid-19 pandemi are disrupting the food security directly such as food system, and indirectly such as household income, food access and health. Examining changes in food and non-food expenditure both before and during the covid-19 epidemic is the goal of this study. In South Sulawesi Province, Indonesia, a descriptive study of both urban and rural areas was employed as the research design. This research uses a cross sectional study research design, the type of data used is secondary data using the 2019-2021 National Socio-Economic Survey data. The results showed that during the pandemic, food expenditure increased, whereas prepared foods, beverages, and cigarette consumption decreased. Different items and services, footwear and hats, as well as party/festival ceremonies, also saw a decrease in non-food expenditure. With a food share of 67,7% in 2020 and 64,3% in 2021, it indicates the presence of food insecurity based on income class (quintiles 1 and 2). In both urban and rural areas, the economic wellbeing level has decreased as a result of the covid-19 pandemic. The conclusion are in South Sulawesi Province the comparison before and during the covid-19 pandemic, food expenditure has increased, non-food expenditure has decreased in 2020 and 2021. People with low incomes are indicated to be food insecure both in urban and rural areas during the Covid-19 pandemic.